The Effect of the Bank Indonesia Interest Rate, Exchange Rate, and Bond Rating against Bond Yield: Registered Corporate Bonds Issuing Company on the Indonesia Stock Exchange - Andini Nurwulandari (International Journal of Science and Society, 2021)
In the current development of the world economic system, movements in the financial system that occur in the world are also affected. Judging from the development of the financial system, it is inseparable from banking, which is an absolute part of it. This condition was reflected in the state of Indonesia during the economic and monetary crisis. This research is a quantitative study with a descriptive analysis approach. The data source is in the form of secondary data obtained from the BEI IBMD 2017-2020. The documentation technique is the data collection technique in this research. All corporate bond issuers listed on the IDx for the 2017-2020 period are the population used in this study. The collection of the samples uses a deliberate sample. In this study the analysis utilizes the determination coefficient, multiple analyzes for linear regression and self-relation. From the above results of discussion and analysis, we can conclude that: 1) the BI rate variable in Indonesia affects bond returns positively and in a significant way in corporate-bond issuing companies; 2) the BT variable affects bond yields in corporate-binding companies; and 3) the BTV has a negative and meaningful effect on bond yields in corporated-bond issuing companies.